Informativeness of various predictors of perioperative cardiovascular complications in non-cardiac surgery - D. A. Sokolov; I. A. Kozlov (Вестник анестезиологии и реаниматологии, 2023)
The objective was to perform a comparative analysis of the information content of potential predictors of cardiovascular complications of various types in patients operated on for vascular diseases.   Materials and Methods. We examined 129 patients aged 66 [61–70] years who underwent elective vascular surgery. We analyzed comorbidity, general clinical indicators, special cardiac risk indices and biomarkers: N-terminal segment of B-type natriuretic peptide prohormone (NT-proBNP) and cardiospecific troponin I. We used logistic regression and ROC analysis.   Results. 21 (16.3 %) perioperative cardiovascular complications were registered in 17 (13.2 %) patients. In one-factor regression, the predictors of cardiovascular complications were coronary heart disease (OR 4.5904; 95 % CI 1.3119–5.9340; p = 0.0171), combination of coronary heart disease and chronic heart failure (OR 2.9419; 95 % CI 1.0140–8.5350; p = 0.047), ASA class > 3 (OR 2.9402; 95 % CI 1.0304–8.3899; p = 0.0438), high cardiac risk surgery (OR 3.4741; 95 % CI 1.1162-10.8126; p = 0.0316), Lee cardiac risk index (OR 2.2353; 95 % CI 1.2842–3.8911; p = 0.0045), the American College of Surgeons cardiac risk index for assessing the risk of perioperative myocardial infarction or cardiac arrest (OR 1.5312; 95 % CI 1.0927–2.1456; p = 0.0133) and the preoperative level of the N-terminal prohormone B-type natriuretic peptide (NT-proBNP) (OR 1.0048; 95 % CI 1.0021–1.0074; p = 0.0004). In multivariate regression, the predictors of cardiovascular complications were high-risk cardiac surgery (OR 5.7439; 95 % CI 1.1027–29.9181; p = 0.0379) and NT-proBNP (OR 1.0044; 95 % CI 1.0015–1.0073; p = 0.0033). The biomarker level > 218 pg/ml discriminated against cardiovascular complications with sensitivity of 82.4 % and specificity of 85.3 % (AUC 0.825; 95 % CI 0.747–0.887; p < 0.0001).   Conclusion. In vascular interventions, the most significant predictors of cardiovascular complications are high-risk cardiac surgery and the preoperative level of NT-proBNP > 218 pg/ml with a sensitivity and specificity level exceeding 80 %.